Peluang dan tantangan kolaborasi aktor negara dan aktor non-negara dalam pemberian bantuan kemanusiaan dari Indonesia ke Palestina (2019–2023) - Fatma Cici Alensia Lingga; Siti Fajrina (Journal of Innovative and Creativity, 2026)
In Collaboration between state and non-state actors plays a crucial role in enhancing the effectiveness of international humanitarian assistance. In Indonesia’s context, the governmentthrough relevant ministries and agencies works alongside various national and international non-governmental organizations to deliver aid to Palestine. This study employs a descriptive-analytical approach, focusing on the period 2019–2023, to both describe and analyze the opportunities and challenges within such collaborations. The findings reveal that these partnerships hold significant potential for accelerating aid distribution, expanding the reach of beneficiaries, and strengthening Indonesia’s humanitarian diplomacy. However, several constraints limit their effectiveness, including armed conflict, regional political tensions, and fluctuating security conditions that affect access and the safety of humanitarian workers. The analysis shows that the success of these collaborations is strongly influenced by the quality of coordination, inter-organizational communication mechanisms, and the actors’ capacity to conduct continuous risk management and access diplomacy. Therefore, strategic planning, active diplomacy, and integrated humanitarian governance are essential to optimizing Indonesia’s role in delivering aid to Palestine.